Statistical optimization and selective uptake of Au(III) from aqueous solution using carbon nanotube-cellulose based adsorbent - BİRTANE, HATİCE; KAHRAMAN, MEMET VEZİR; YILDIZ, NİLGÜN (ELSEVIER, 2022)
In this study, a carbon nanotube cellulose-based UV-curable nanocomposite was prepared as an adsorbent to selectively separate Au (III) ions from an aqueous medium. For this purpose, thiol-functionalized carbon nanotube and acrylate-functionalized hydroxyethyl cellulose were synthesized and the photo-curable adsorbent was obtained using the thiol-ene click reaction. The FTIR spectra revealed that the thiol groups and acrylate groups were successfully attached to carbon nanotube and hydroxyethyl cellulose, respectively. Moreover, the Scanning Electron Microscopy-Energy Dispersive X-Ray analyses showed that the photo-curable adsorbent contained sulfur atoms, thus indicating successful modification. The parameters affecting the recovery of the Au (III) ions were determined using the Plackett-Burman method. The optimum values of the parameters, which were pH, adsorption time, initial Au (III) concentration, and adsorbent amount were determined using the Box-Behnken method. The Langmuir adsorption isotherm was determined to be the best equation to describe the interaction of the Au (III) ions with the adsorbent (R-2: 0.995). The examination of the effectiveness of the photocurable adsorbent in the presence of different metal ions yielded prosperous results. Also, the developed method has been successfully applied for the recovery of Au(III) ions in river waters.
Keywords: Au (III); Uptake; Carbon nanotube; Thiol-ene dick; Photo-curable; Box-Behnken design; HEAVY-METAL IONS; EFFICIENT REMOVAL; GOLD; ADSORPTION; CR(VI); NANOCOMPOSITE; EXTRACTION; GOLD(III)